Perancangan dan Penerapan Competency Matrix Berbasis Website pada Departemen HRBP on Produksi PT Dirgantara Indonesia - Siti Rahma Darya; Mohammad Rizal Gaffar (Applied Business and Administration Journal, 2024)
The HRBP Non-Production Department of PT Dirgantara Indonesia faces challenges in effectively and efficiently managing employee competency mapping. The limitations in managing employee competency information result in difficulties in identifying development needs and making decisions related to human resources. This project aims to design and implement a competency matrix-based website for the HRBP Non- Production Department of PT Dirgantara Indonesia. The primary objective of this project is to enhance the effectiveness and efficiency of managing employee competency mapping and facilitate decision-making related to human resource development by the HRBP Non-Production Department. The project adopts a system development approach based on the SDLC (System Development Life Cycle), consisting of several stages including needs analysis, system design, website development, and testing. By utilizing the SDLC methodology, this project ensures that the development of the competency matrix website in the HRBP Non- Production Department of PT Dirgantara Indonesia is conducted in a structured and systematic manner, providing a user-friendly interface. The result of this project is an effective and efficient competency matrix website for managing and presenting employee competency information. Testing conducted indicates that the system functions well.